(untitled) - Carrick, Carol; Carrick, Donald (New York, 1985)
Lucy and her younger brother examine their feelings about a mentally handicapped boy they both fear when he follows them home one snowy day.
Keywords: Mentally handicapped; Fiction; Children's stories, American